Risk and childhood poverty: notes from theory and research - Hardgrove, A; Enenajor, A; Lee, A (Young Lives, 2011)
Chronic childhood poverty is often considered synonymous with the risk of adverse outcomes. In this paper, we consider the ways in which notions of risk, poverty and childhood are constructed and supported through empirical research. We find that poverty and childhood are often implicitly assumed to be conditions that place young human beings at greater risk. We review the differences between how poverty has been defined and conceptualised, and how it is experienced as a lived reality. We discuss how risk is constituted and approached as a subject of empirical research. Finally, we turn our attention to the discourses, debates and theories concerning universal childhoods and therefore, universal risks to children. We then reflect on contributions from human development research that inform notions of risk to children. In conclusion, we argue that any evaluation of risk in contexts of chronic childhood poverty must include both the structural implications and complexities of poverty in a given context, as well as the multidimensional nature of growth and development among poor children.